The judicial reform Ukraine: administrative and legal basis - Квасневська, Наталя Дмитрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article deals with the essence of judicial reform in Ukraine, which provides prompt and effective judicial protection of its citizens and other individuals and legal entities, state and public interests. An important area for further development of the judicial system must be as effective implementation of mechanisms to combat corruption among judges, the final release of the judiciary from political pressure and influence from the other branches of government, as well as enhancing the role of civil society in monitoring the work of the judiciary. Relevance of the topic is that during the time that has elapsed since Ukraine gained independence, our country has passed a long and difficult way towards the formation of an independent and efficient judicial system that would ensure the speedy and effective judicial protection of its citizens and other legal entities and individuals, state and public interests. However, today there are many unresolved problems to overcome are to be directed further efforts of the state. This situation is due to the ineffectiveness of certain aspects of the state policy in the sphere of organization and functioning of the judicial system. mistakes made at various stages of its formation. Thus, the study of the history of the state policy in the sphere of organization and functioning of the judicial system of Ukraine will determine its main shortcomings and areas for further development. Also, the relevance of the research topic is confirmed insufficiency of scientific papers dealing with the administrative and legal framework of reform of the judicial system of Ukraine, which, combined with the need for complex scientific analysis of this issue leads to the importance and timeliness of this article. The aim of the article is to define the legal and administrative aspects of the reform of the judicial system of Ukraine. The findings are that important direction for further development of the judicial system should be as the introduction of mechanisms to effectively fight corruption among judges, the final release of the judiciary from political pressure and influence from the other branches of government, as well as enhancing the role of civil society in monitoring the work of the judiciary. Therefore, the further development of public policy should be concentrated in the Concept of development of the judicial system for the coming years, the development of the provisions of which should be the direction of future research.